2019
DOI: 10.1002/jcb.29508
|View full text |Cite
|
Sign up to set email alerts
|

Formin mDia1 contributes to migration and epithelial‐mesenchymal transition of tubular epithelial cells exposed to TGF‐β1

Abstract: Renal tubular epithelial cells may undergo epithelial‐mesenchymal transition (EMT) in response to stimuli, such as transforming growth factor (TGF)‐β1, leading to myofibroblast activation and renal fibrosis. The formin mDia1 is required for nucleation and polymerization of actin and the microtubule cytoskeleton. The present study sought to explore the role of mDia1 in EMT of tubular epithelial cells. A rat model of unilateral ureteral obstruction (UUO) was established. The expression of TGF‐β1, collagen I, col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 48 publications
1
4
0
Order By: Relevance
“…The immunofluorescence and Western blotting analysis confirmed our speculation because of the alteration in epithelial-mesenchymal markers after DpdtC treatment (Figure 4), in accordance with others observation [45]. To corroborate the ability of DpdtC in induction, the EMT model that induced by TGF-β1 needed to be established for this method has been widely accepted in molecular biology [46]. It was interesting that DpdtC abolished the action of TGF-β1 on EMT induction in the present study ( Figure 5), demonstrating that DpdtC was able to inhibit EMT, which was in accordance with the action of the iron chelator reported previously [47].…”
Section: Discussionsupporting
confidence: 90%
“…The immunofluorescence and Western blotting analysis confirmed our speculation because of the alteration in epithelial-mesenchymal markers after DpdtC treatment (Figure 4), in accordance with others observation [45]. To corroborate the ability of DpdtC in induction, the EMT model that induced by TGF-β1 needed to be established for this method has been widely accepted in molecular biology [46]. It was interesting that DpdtC abolished the action of TGF-β1 on EMT induction in the present study ( Figure 5), demonstrating that DpdtC was able to inhibit EMT, which was in accordance with the action of the iron chelator reported previously [47].…”
Section: Discussionsupporting
confidence: 90%
“…So far, we focused on the protein diaphanous homolog 1 (DIAPH1) belonging to the family of formin proteins and recently described to promote myofibroblastic activation of HSCs. [36][37][38] Indeed, this protein was found as the most upregulated in T0, and worthy of note, also in T6 samples despite viral clearance. With the intent to validate this evidence by means of a different approach and in order to extend it to a broader patient group, western blot analysis was performed on 14 HD and 20 longitudinally enrolled HCV patient (T0 and T6) EV samples.…”
Section: Structural Analysis: Circulating Ev Proteomic Analysismentioning
confidence: 81%
“…DIAPH1 has a key role in myofibroblast differentiation and is involved in actin nucleation/ elongation and ACTA2 induction. 37,38 Notably, it has recently been shown that DIAPH1 stimulates myofibroblastic activation of HSCs, promoting the endocytosis of TGFbRII 36 ; it may also contribute to HSC activation by favoring the formation of ACTA2positive stress fibers. Moreover, DIAPH1 inactivation suppresses HSCs' tumor-promoting effects in a tumor implantation mouse model.…”
Section: Discussionmentioning
confidence: 99%
“…Formins are responsible for the linear polymerisation of F-actin in filopodia while fascin cross-links the formed filaments in parallel bundles [ 68 , 69 ]. Formation of filopodia [ 70 , 71 ] downstream of activation of TWIST1 and SNAIL1 [ 72 ] and the expression of formins [ 73 , 74 ] regulate the migration of cancer cells undergoing EMT. Additionally, the upregulation of formins contributes to metastasis formation [ 75 ], and high levels of fascin correlate with poor prognosis in a number of cancers including breast, lung, gastrointestinal and oral squamous cell carcinoma [ 64 , 76 , 77 ], suggesting that their role in EMT contributes to cell invasion and the formation of secondary tumour foci.…”
Section: Invasive Adhesions Formed By Cells Undergoing Emt In Solid T...mentioning
confidence: 99%